Effects of simvastatin on the expression of inducible nitric oxide synthase and brain-derived neurotrophic factor in a lipopolysaccharide-induced rat model of Parkinson disease. (3rd March 2016) - Tan, Wang; Xue-bin, Cao; Tian, Zhang; Xiao-wu, Chen; Pei-pei, Huang; Zhi-bin, Chen; Bei-sha, Tang
Abstract : Objective : To investigate the effects of simvastatin on the expression of inducible nitric oxide synthase (iNOS) and brain-derived neurotrophic factor (BDNF) in the substantia nigra in a lipopolysaccharide (LPS)-induced rat model of Parkinson disease (PD), and to study the mechanisms underlying the neuroprotective effects of simvastatin in PD. Methods : The LPS-PD model was established by injection of LPS (5 mg/mL, 2.0 μL) into the right substantia nigra compacta (SNC). Rats in the sham-operated group received saline. The simvastatin treatment group was intraperitoneally administered simvastatin (5 mg/kg, 2.0 μL) at 1 h before, and daily for 14 days after surgery, while the sham-operated and LPS-model groups received saline. Iba-1-positive cells and tyrosine hydroxylase (TH), as well as iNOS and BDNF in the SNC were detected by immunohistochemistry and Western blotting, respectively. The effect of simvastatin in the PD model was also examined in behavioral tests. Results : The LPS-model group exhibited typical animal PD behaviors. Compared with the control group, the LPS-model group exhibited a decreased number of DA neurons ( p < 0.01) in the SNC, as well as increases in the Iba-1-positive cell number and iNOS expression ( p < 0.05), while BDNF expression was downregulated ( p < 0.01). These effects were inhibited by simvastatin treatment ( p < 0.05). Conclusion : Simvastatin mediates a protective effect on dopaminergic neurons in the SNC in the LPS-PD model, possibly by promoting neuronal repair and regeneration, and by inhibiting oxidative stress, thus improving substantia nigra function.